Respuesta :

Answer:

Step-by-step explanation:

To find the inverse function, the first step we do is change f(x) to Y. So now, we have

y=2x+1

Now that we have this function, we simply flip x and y. When we do that, we get

x=2y+1

Now that we have this function, we just solve for Y. We do that by bring 1 to the other side by subtracting it from both sides, then dividing both sides by 2.

x-1=2y+1-1

x-1=2y

(x-1)/2=2y/2

(x-1)/2=y

So, our inverse function is:

y=(x-1)/2, or y=x/2 - 1/2

Hope I helped!